Elusive intensities, fleeting seductions, affective voices - Paasonen Susanna (My University, 2025)
As a genre, pornography aims to move its readers and viewers in corporeal ways. Scholarly work examining its conventions and codes may emulate some of this carnal address or, alternatively, firmly hold the materials studied at arm’s length. With different strategies of academic writing come different proximities and distances that set the stage for certain forms of reader engagement. Zooming in on proximities where the intensities of text set the bodies of readers and writers into motion, this article explores the role and function of that which Gregg identifies as the writer’s affective voice in feminist cultural studies inquiry. Writing on and with affect means being both invested in and infected by the worlds studied. In studies of pornography, this is a means to communicate the particularities of the materials examined, the bodily resonances they evoke and the political stakes that they involve.